MOTIVASI BELAJAR SISWA DITINJAU DARI SELF-DETERMINATION THEORY: STUDI DI SMA PLUS AL GHIFARI - Sri Wahyuni; Nina Amelia; Ahmad Nazar Fakhury; Fenia Marliana; Tarsono Tarsono (EDUPEDIA, 2026)
The Indonesian nation is currently facing a serious issue in the form of learning loss, marked by decreased motivation, learning ability, and academic achievement of students, including at SMA Plus Al Ghifari. This condition is evident from passive learning attitudes, lack of attention to teachers, no preparation for learning at home, and an inability to complete assignments. This study employs a case study method based on Self-Determination Theory (SDT) to examine students' learning motivation and the factors influencing it. The findings indicate that motivation plays an important role as a driver of learning activities and a determinant of educational success. Field findings reinforce previous research that high motivation increases enthusiasm, perseverance, and achievement, whereas low motivation leads to indifference and learning difficulties. This study underscores the need to strengthen intrinsic and extrinsic motivation, and the active role of teachers in providing positive support and the creation of a conducive learning environment to overcome learning loss and improve the quality of education in schools.